Blockade of the protease ADAM17 ameliorates experimental pancreatitis - Saad, Mohamed I; Weng, Teresa; Lundy, Joanne; Gearing, Linden J; West, Alison C; Harpur, Christopher M; Alanazi, Mohammad; Hodges, Christopher; Croagh, Daniel; Kumar, Beena; Sagi, Irit; Rose-John, Stefan; et al. (Proceedings of the National Academy of Sciences - PNAS, 2022)
Acute and chronic pancreatitis, the latter associated with fibrosis, are multifactorial inflammatory disorders and leading causes of gastrointestinal disease-related hospitalization. Despite the global health burden of pancreatitis, currently, there are no effective therapeutic agents. In this regard, the protease A Disintegrin And Metalloproteinase 17 (ADAM17) mediates inflammatory responses through shedding of bioactive inflammatory cytokines and mediators, including tumor necrosis factor α (TNFα) and the soluble interleukin (IL)-6 receptor (sIL-6R), the latter of which drives proinflammatory IL-6 trans-signaling. However, the role of ADAM17 in pancreatitis is unclear. To address this, mice-which are homozygous for the hypomorphic allele resulting in marked reduction in ADAM17 expression-and their wild-type (WT) littermates were exposed to the cerulein-induced acute pancreatitis model, and acute (1-wk) and chronic (20-wk) pancreatitis models induced by the cigarette smoke carcinogen nicotine-derived nitrosamine ketone (NNK). Our data reveal that ADAM17 expression was up-regulated in pancreatic tissues of animal models of pancreatitis. Moreover, the genetic ( mice) and therapeutic (ADAM17 prodomain inhibitor [A17pro]) targeting of ADAM17 ameliorated experimental pancreatitis, which was associated with a reduction in the IL-6 trans-signaling/STAT3 axis. This led to reduced inflammatory cell infiltration, including T cells and neutrophils, as well as necrosis and fibrosis in the pancreas. Furthermore, up-regulation of the ADAM17/IL-6 trans-signaling/STAT3 axis was a feature of pancreatitis patients. Collectively, our findings indicate that the ADAM17 protease plays a pivotal role in the pathogenesis of pancreatitis, which could pave the way for devising novel therapeutic options to be deployed against this disease.